Effectiveness Observation of Conjunctival Flap Transposition Combined With Placement of Lacrimal Ducts for the Repair of Eyelid Tumor Excision Involving the Lacrimal Point - Zhiyun Zhan; Jingjin Zhang; Enna Huang; Qiang Qu; Ting Wang; Tingting Wang (Journal of Ophthalmology)
Conclusions: Conjunctival flap transposition and artificial lacrimal duct placement is an effective surgical approach for the repair of defects following lacrimal punctum tumor excision. The method not only preserves lacrimal duct function but also achieves satisfactory esthetic results, making it a reliable choice for clinical application.